Relating on-field youth football head impacts to pneumatic ram laboratory testing procedures. (March 2021) - Campolettano, Eamon T; Rowson, Steven
A youth-specific football helmet testing standard has been proposed to address the physical and biomechanical differences between adult and youth football players. This study sought to relate the proposed youth standard-defined laboratory impacts to on-field head impacts collected from youth football players. Head impact data from 112 youth football players (ages 9–14) were collected through the use of helmet-mounted accelerometer arrays. These head impacts were filtered to only include those that resided in corridors near prescribed National Operating Committee on Standards for Athletic Equipment (NOCSAE) impact locations. Peak linear head acceleration and peak rotational head acceleration magnitudes collected from pneumatic ram impactor tests as specified by the proposed NOCSAE youth standard were compared to the distribution of on-field head impacts. All laboratory impact tests were among the top 10% in terms of magnitude for Severity Index and peak rotational acceleration of matched location head impacts experienced by youth football players. As concussive head impacts are among the most severe impacts experienced on the field, a safety standard geared toward mitigating concussion should assess the most severe on-field head impacts. This proposed testing standard may be refined as more becomes known regarding the biomechanics of concussion among youth athletes.